2021
DOI: 10.3390/ijms22147499
|View full text |Cite
|
Sign up to set email alerts
|

Treat Me Well or Will Resist: Uptake of Mobile Genetic Elements Determine the Resistome of Corynebacterium striatum

Abstract: Corynebacterium striatum, a bacterium that is part of the normal skin microbiota, is also an opportunistic pathogen. In recent years, reports of infections and in-hospital and nosocomial outbreaks caused by antimicrobial multidrug-resistant C. striatum strains have been increasing worldwide. However, there are no studies about the genomic determinants related to antimicrobial resistance in C. striatum. This review updates global information related to antimicrobial resistance found in C. striatum and highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 90 publications
(178 reference statements)
2
24
0
Order By: Relevance
“…The dissemination of multidrug-resistant Corynebacterium species in the hospital environment affects the acquired resistance to β-lactam antimicrobials, clindamycin, erythromycin, ciprofloxacin, and gentamicin [18]. Currently, glycopeptides, linezolid, quinupristin/dalfopristin, daptomycin, and tigecycline are the effective drugs available against C. striatum clinical isolates [19][20][21]. Unfortunately, the literature is scarce and related to specific countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissemination of multidrug-resistant Corynebacterium species in the hospital environment affects the acquired resistance to β-lactam antimicrobials, clindamycin, erythromycin, ciprofloxacin, and gentamicin [18]. Currently, glycopeptides, linezolid, quinupristin/dalfopristin, daptomycin, and tigecycline are the effective drugs available against C. striatum clinical isolates [19][20][21]. Unfortunately, the literature is scarce and related to specific countries.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the literature is scarce and related to specific countries. However, the increasing resistance is expected to be a key problem for the genus in the future [21].…”
Section: Introductionmentioning
confidence: 99%
“…The plasmids in bacteria provide a positive platform to capture and spread a variety of ARG. In corynebacteria of clinical importance, several plasmids are known to confer resistance ( Deb and Nath, 1999 ; Leyton et al, 2021 ), such as pTP10 of C. striatum , pNG2 of Corynebacterium diphtheriae , and pJA144188 of Corynebacterium resistens . They also include a significant content of insertion sequences ( Tauch et al, 2003 ; Schröder et al, 2012 ), suggesting a relation between IS, plasmids, and C. striatum .…”
Section: Why Should Insertion Sequences Be An Epidemiological Descriptor?mentioning
confidence: 99%
“…Furthermore, this extends to other plasmids and other bacteria; for example, Che et al (2021) showed that IS contribute to the acquisition and transfer of ARG in conjugative plasmids. Regardless of the existence of plasmids, something that is quite clear is the relationship of IS with antibiotic resistance in C. striatum ( Wang et al, 2020 ; Leyton et al, 2021 ). Therefore, the increase in resistance in C. striatum strains would be mainly associated with these mobile elements.…”
Section: Why Should Insertion Sequences Be An Epidemiological Descriptor?mentioning
confidence: 99%
See 1 more Smart Citation